‘Daring Leaps’ Construction of Meaning and Individual Agency in Career Change Narratives in the Media - LaPointe, Kirsi; Heilmann, Pia (Nordic Journal of Working Life Studies, 2014)
The role of individual agency in crafting meaningful work has attracted increasing interest in recent studies of careers and working life. The purpose of this paper is to make visible the role of the media in reproducing and shaping understandings of careers and agency. By analyzing narratives of career change in the Finnish media, we identify three types of narrative and show how they construct meaningful careers by juxtaposing the past and present work in terms of setting, status, meaning, pace, and workload. Overall, these narratives depict a shift from traditional careers toward work that is concrete, meaningful, of lower status, and less hectic. Moreover, the narratives represent career changers as self-reliant heroes taking “daring leaps.” Hence, we argue that the media reproduces individualistic assumptions of careers and reinforces the dominant, neoliberal ideal of self-responsible, autonomous subjects. We conclude by calling for alternative narratives that recognize the need for more meaningful careers but help strengthen agency in a less individualistic fashion.